Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1097/01.wcb.0000055177.50448.fa
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Body Temperature and Neuroprotection by Endogenous Interleukin-6 in Cerebral Ischemia

Abstract: Summary:Although the function of fever is still unclear, it is now beyond doubt that body temperature influences the outcome of brain damage. An elevated body temperature is often found in stroke patients and denotes a bad prognosis. However, the pathophysiologic basis and treatment options of elevated body temperature after stroke are still unknown. Cerebral ischemia rapidly induced neuronal interleukin-6 (IL-6) expression in mice. In IL-6-deficient mice, body temperature was markedly decreased after middle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(28 citation statements)
references
References 64 publications
2
24
0
2
Order By: Relevance
“…On the other hand, the results that IL-6 upregulated CaN expression and activity in the presence of NMDA suggest that microenvironments around or/and within injured neurons, such as excessive Ca 2+ , may help to activate IL-6 signaling pathway. It has been shown that IL-6 level increases dramatically in many neurological disorders [12][13][14][15]. The increased IL-6 exerts compensatory neuroprotection against further neuronal injury or death [60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the results that IL-6 upregulated CaN expression and activity in the presence of NMDA suggest that microenvironments around or/and within injured neurons, such as excessive Ca 2+ , may help to activate IL-6 signaling pathway. It has been shown that IL-6 level increases dramatically in many neurological disorders [12][13][14][15]. The increased IL-6 exerts compensatory neuroprotection against further neuronal injury or death [60].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 expression is low in the brain under normal conditions, but it increases dramatically in some neurological disorders, such as stroke, brain damage and seizures [12][13][14][15]. IL-6 role in the brain is complicated.…”
Section: Introductionmentioning
confidence: 98%
“…In another report, GCA patients with ischemic events had lower IL-6 mRNA tissue expression and lower circulating IL-6 levels, while, compared to patients without ischemia, no significant differences were found for IL-1b and tumor necrosis factor 17 . IL-6 is known to be associated with fever 18,22 . In addition, angiogenesis in temporal artery sections was more prominent in patients with strong acute phase response, and in those without ischemic complications 6 .…”
Section: Systemic Manifestations and Inflammatory Responsementioning
confidence: 99%
“…IL-6 and its receptor (IL-6R) are expressed in neurons after ischemia (29)(30)(31), and it has been shown that i.c.v. injection of IL-6 in rats decreases the infarct volume (32), and endogenous IL-6 also plays a neuroprotective role through thermoregulation (33). More recently, IL-6R antibody injection increased infarct volume after ischemia (34).…”
mentioning
confidence: 99%